Koti, hyvinvointityö ja haavoittuvuus - Günther, Kirsi; Holmberg, Suvi; Juhila, Kirsi; Kiuru, Hilla; Lämsä, Riikka; Niemi, Mia; Outila, Marjo; Perälä, Riikka; Raitakari, Suvi; Ranta, Johanna; Räsänen, Jenni-Mari; Saario, Sirpa; et al. (Tampere University Press, 2022)
In this book [titled Home, welfare work and vulnerability] the authors take the reader on welfare workers’ home visits to clients in need of support in their living. Welfare workers refer to professionals in health and social care who in the book are represented among others by social workers, social care workers and nurses. The main concepts of the book are home, welfare work and vulnerability and these are contemplated from different angles. Welfare work entails encountering people who are in vulnerable situations in the midst of their everyday lives. They may need support in coping with their mental health, with physical illnesses, with the challenges of achieving sobriety and recovery or perhaps with the difficulties accompanying old age. On the one hand their ability to act is limited and weak but on the other they have many kinds of strengths and resources.